2019
DOI: 10.9734/jammr/2019/v29i1130141
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Pollution and Decrease Neuroplasticity in Brain Development of the Ogoni Children in Rivers State, Nigeria

Abstract: Background: Health and mental related illnesses has emerged as a new challenge in the rural and undeveloped areas in Ogoniland where petroleum exploration activities have devastated the entire ecosystem. Many of the school children are no longer zealous about their academic activities, as their performances in school are always very poor. It has been reported that the children’s poor performance in school is closely linked with several health and mental challenges suffered by these children in the highly pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Agriculture has been known to produce significant effect on climate change primarily through the production and release of greenhouse gasses such as carbon dioxide, methane, and nitrous oxide [44]. Also a form of agriculture that practises tillage, fertilization, and pesticide application also releases ammonia nitrate, phosphorus and many others pesticides that affect air, water, and soil quality as well as biodiversity [45,46].…”
Section: Agriculturementioning
confidence: 99%
“…Agriculture has been known to produce significant effect on climate change primarily through the production and release of greenhouse gasses such as carbon dioxide, methane, and nitrous oxide [44]. Also a form of agriculture that practises tillage, fertilization, and pesticide application also releases ammonia nitrate, phosphorus and many others pesticides that affect air, water, and soil quality as well as biodiversity [45,46].…”
Section: Agriculturementioning
confidence: 99%
“…Unfortunately, the atmosphere also contains pollutants which affect health [8] . Pollution is generally the introduction by mankind into the environment substances liable to cause hazards to human health, harm to the living organism and ecological system [1,9] , damage to structure or interfere with the legitimate uses of the environment [32,34,35] . Air pollution is on the increase especially in highly urbanized and industrialized cities [4,16,25] .…”
Section: Introductionmentioning
confidence: 99%
“…The health effect of air pollution on humans includes carcinogenicity, pulmonary tuberculosis, cerebrospinal meningitis, pneumonia, whooping cough and measles [8,9] . Particulate Matter can also comprise toxic pollutants, such as heavy metals, polycyclic aromatic hydrocarbons (PAHs), and other particle-bound organic compounds, which may be responsible for activating local lung damage particularly when the particles deposit on the epithelial surfaces [24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Niger Delta is among the ten most important wetlands and marine ecosystems in the world [10]. The oil industries located within this region has also contributed immensely to the growth and development of the country, which is a fact that cannot be disputed [11], but unsustainable oil exploration activities has rendered the Niger Delta region, to be one of the five most severely petroleum damaged ecosystems in the world [12,11]. Studies have shown that the quantity of oil spilled over the last 50 years in Nigeria was a least 9-13 million barrels, which is equivalent to 50 Exxon Valdez spills [6,13].…”
Section: Introductionmentioning
confidence: 99%